Chilling a hot planet: Many solutions, no answers - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
If there was a report card on how the world is doing on issues related to climate change, it would read a resounding 'F'. Consider the figures. It took about 12,500 years between the last glacial age and today for global temperatures to rise six degrees Celsius. Yet in this century alone – despite heightened awareness of the need to arrest the ever-increasing levels of greenhouse gas emission – temperatures have risen up to four degrees Celsius.